2021
DOI: 10.1155/2021/5524566
|View full text |Cite
|
Sign up to set email alerts
|

Increased Circulatory Interleukin-17A Levels in Patients with Progressive and Leukotrichial Vitiligo

Abstract: Background. Vitiligo is a chronic condition characterized by skin depigmentation. Although not life-threatening, it significantly impacts quality of life. The pathophysiology of vitiligo remains poorly understood, and treatment options are limited. Mounting evidence supports the importance of autoreactive T cells and, particularly interleukin-17A- (IL-17A-) secreting Th17 cells, in vitiligo. IL-17A targeting has been proven successful in various inflammatory dermatological conditions, including psoriasis and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…In this study, we also detected that serum level of IL‐38 was correlated negatively with the age of patients and the age of disease onset. Similarly, Le et al 17 demonstrated that serum IL‐17A level correlated negatively with the age of vitiligo patients and their age of disease onset. The authors assumed that the higher cytokine level in young patients might be caused by mental stress experienced by younger age groups, which plays a role in inducing vitiligo by exacerbating immunological dysregulation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, we also detected that serum level of IL‐38 was correlated negatively with the age of patients and the age of disease onset. Similarly, Le et al 17 demonstrated that serum IL‐17A level correlated negatively with the age of vitiligo patients and their age of disease onset. The authors assumed that the higher cytokine level in young patients might be caused by mental stress experienced by younger age groups, which plays a role in inducing vitiligo by exacerbating immunological dysregulation.…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, vitiligo activity was reported to be associated with overexpression of Th1 (TNF‐α and interferon‐γ 16 ) and Th17 cytokines (IL‐17A). 17 Taking together, the enhanced pro‐inflammatory cytokines in patients with signs of vitiligo activity might have further enhanced IL‐38 expression from monocytes and keratinocytes as an attempt to counteract the overexpression of these pro‐inflammatory cytokines. Indeed, signs of vitiligo activity have recently been recognized as crucial in clinical practice for initiating therapy to prevent disease progression 10…”
Section: Discussionmentioning
confidence: 99%
“…Th1 and Th17 cell activation pathway is one of the main autoimmune etiologies of vitiligo, 3 reinforced by reported raised or imbalanced level of IL‐17 in sera or skin biopsies of vitiligo patients, 4,38,44,47,61,62,75,87,93,94,102–105 highlighting the remarkable IL‐17 action in the initiation and, more importantly, the development of vitiligo 55,91 …”
Section: Resultsmentioning
confidence: 99%
“…Studies have reported a correlation between the extent of depigmentation and increased level of IL‐17 in sera or lesion biopsy in vitiligo patients 55,92–94 ; as well as the existence of IL‐17 genotype 95,96 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation